DNA methyltransferase 3A controls intestinal epithelial barrier function and regeneration in the colon - Antonella Fazio; Dora Bordoni; Jan W. P. Kuiper; Saskia Weber-Stiehl; Stephanie T. Stengel; Philipp Arnold; David Ellinghaus; Go Ito; Florian Tran; Berith Messner; Anna Henning; Joana P. Bernardes; et al. (Nature Communications, 2022)
DNA methyltransferase 3 A (DNMT3A) is involved in DNA methylation, and genetic variants in the DNMT3 locus have been associated with inflammatory bowel disease. Here the authors report that DNMT3A controls intestinal epithelial barrier function and restoration of the gut barrier function after intestinal epithelial perturbation.